Impending doom: The loss of diversification before a crisis - Libin Yang; William Rea; Alethea Rea (International Journal of Financial Studies, 2017)
We present four methods of assessing the diversification potential within a stock market, and two of these are based on principal component analysis. They were applied to the Australian stock exchange for the years 2000 to 2014 and all show a consistent picture. The potential for diversification declined almost monotonically in the three years prior to the 2008 financial crisis, leaving investors poorly diversified at the onset of the Global Financial Crisis. On one of the four measures, the diversification potential declined even further in the 2011 European debt crisis and the American credit downgrade.
Keywords: G11; 330; principal component analysis; stock selection; diversification; stock portfolios; ASX200